Nephroprotective Effect of the Leaf Extract of Ajuga remota Benth Against Gentamicin-Induced Nephrotoxicity in Swiss Albino Mice - Akinaw MA; P Nair SK; Usure RE; Leta B; Kedir A; Mola SA; Waritu NC; Jemal M; Mulat BK (Journal of Experimental Pharmacology, 2024)
Metages Ayele Akinaw,1 Suresh Kumar P Nair,1 Rashed Edris Usure,2 Bati Leta,1 Abdo Kedir,3 Selam Ayele Mola,4 Nuredin Chura Waritu,5 Mohammed Jemal,6 Berhane Kebede Mulat1 1Department of Biomedical Sciences, School of Medicine, Jimma University, Jimma, Ethiopia; 2Department of Pharmaceutical Chemistry, School of Pharmacy, Hawassa University, Hawassa, Ethiopia; 3Department of Pathology, School of Medicine, Jimma University, Jimma, Ethiopia; 4Department of Adult Health Nursing, School of Nursing, Jimma University, Jimma, Ethiopia; 5Department of Biomedical Sciences, School of Medicine, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 6Department of Biomedical Sciences, School of Medicine, Debre Merkos University, Debre Merkos, EthiopiaCorrespondence: Nuredin Chura Waritu, Tel +251919617254, Email nurmaye12@gmail.comBackground: Drug-induced kidney injury was among the most common renal damages, from which gentamicin occupies around 25% of this injury. Gentamicin-induced renal damage is caused by increased free radicals with subsequent amplified inflammation. Ajuga remota leaf extract has many phytochemicals with antioxidant activities, which may improve gentamicin-induced renal damage. Thus, we aimed to investigate the nephroprotective effect of Ajuga remota leaf methanolic extract on gentamicin-induced nephrotoxicity in Swiss Albino Mice.Methods: An experimental study design was used on 30 experimental mice randomly allocated in six groups: Group I, II, II, IV, and VI, among which mice were given only distilled water, only gentamicin, 600 mg/kg Ajuga remota leaf extract only, gentamicin along with 200 mg/kg extract, gentamicin with 400 mg/kg extract and gentamicin with 600 mg/kg extract, respectively. At the end of the experiment, the mice were sacrificed after being anaesthetized, and blood samples were collected through a cardiac puncture for renal function tests while the kidneys were removed for histopathological evaluation. The data were entered into Epidata version 4.6 and exported to SPSS version 25 for further analysis using one-way analysis of variance. Statistical significance was set at p < 0.05.Results: Group II mice had significantly higher levels of serum creatinine and blood urea levels compared to group I and III. The body weight of the mice in group V and group VI showed a significant increase compared with Group II. Serum creatinine and blood urea levels were reduced significantly in the Ajuga remota leaf extract administered group of mice compared to group II. Abnormal kidney architectural changes were seen among group II mice; however, those changes were improved after administration of Ajuga remota leaf methanolic extract.Conclusion: Methanol extract of Ajuga remota leaf provided effective protection against gentamicin-induced oxidative renal damage through its antioxidant effects.Keywords: Ajuga remota Benth, gentamicin, nephrotoxicity, methanol